2016
DOI: 10.1590/1678-457x.0020
|View full text |Cite
|
Sign up to set email alerts
|

Fresh pasta enrichment with protein concentrate of tilapia: nutritional and sensory characteristics

Abstract: With the goal of developing and characterizing the nutritional and sensory aspects of fresh pasta supplemented with tilapia protein concentrate, four types of pasta were prepared, with inclusion of 0, 10, 20, or 30% of tilapia protein concentrate. Linear effects were observed (P < 0.01) in crude protein, total lipids, ash, carbohydrate, and caloric values; these parameters increased with increasing amounts of tilapia protein concentrate in the pasta. The concentration of Na, P, Ca, Mg, and Zn increased linearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 20 publications
4
39
0
10
Order By: Relevance
“…Similar results were obtained by Goes et al (2016), who included different levels (0, 10, 20 and 30%) of tilapia meal into fresh pasta and verified a linear increase in lipid and ash content, with a decrease in carbohydrate content.…”
Section: Chemical Composition and Calorific Valuesupporting
confidence: 87%
“…Similar results were obtained by Goes et al (2016), who included different levels (0, 10, 20 and 30%) of tilapia meal into fresh pasta and verified a linear increase in lipid and ash content, with a decrease in carbohydrate content.…”
Section: Chemical Composition and Calorific Valuesupporting
confidence: 87%
“…These results demonstrate that inclusion of fishmeal is effective to enrich bread with protein and other products such as pasta (Goes et al, 2016); khitchri (Hussain et al, 2007), snacks (Justen et al, 2016), salt biscuits (Ibrahim, 2009), among other products.…”
Section: Resultsmentioning
confidence: 86%
“…In pasta with different levels of inclusion (0, 10, 20 and 30%) Nile tilapia meal, Goes et al (2016) observed a linear increase in the concentrations of calcium, phosphorus, magnesium, sodium and zinc, showing that the inclusion of tilapia meal can improve the mineral profile of the product.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies observed the nutritional and physicochemical aspects of dried pasta manufactured with the mince and the oil of Sardinella longiceps [14], Catla Catla mince [15], and fresh pasta enriched with protein concentrate of tilapia [16]. However, as nutritional composition and chemical stability vary depending on fish species and the processing procedure [4,17,18], the physicochemical properties of dried pasta manufactured with partial replacement of wheat flour by tilapia flour is still unknown.…”
Section: Introductionmentioning
confidence: 99%